Architecture, power and religion in Lebanon : Rafiq Hariri and the politics of sacred space in Beirut - Vloeberghs, Ward. (Social, Economic and Political Studies of the Middle East and Asia, 2015)
In Architecture, Power and Religion in Lebanon , Ward Vloeberghs explores Rafiq Hariri's patronage and his posthumous legacy to demonstrate how religious architecture becomes a site for power struggles in contemporary Beirut. By tracing the 150 year-long history of the Muhammad al-Amin Mosque - Lebanon's principal Sunni mosque - and the subsequent development of the site as a commemoration venue, this account offers a unique illustration of how architecture, religion and power become discursively and visually entangled. Set in a multi-confessional society marked by social inequalities and political fragmentation, this interdisciplinary study analyses how architectural practice and urban reconfigurations reveal a nascent personality cult, communal mourning, and the consolidation of political territory in relation to constantly shifting circumstances.